2018
DOI: 10.1101/478453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reverse vaccinology approach to design a novel multi-epitope subunit vaccine against avian influenza A (H7N9) virus

Abstract: 32 33 H7N9, a novel strain of avian origin influenza was the first recorded incidence where a human was 34 transited by a N9 type influenza virus. Effective vaccination against influenza A (H7N9) is a major 35 concern, since it has emerged as a life threatening viral pathogen. Here, an in silico reverse 36 vaccinology strategy was adopted to design a unique chimeric subunit vaccine against avian 37 influenza A (H7N9). Induction of humoral and cell-mediated immunity is the prime concerned 38 characteristics f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 65 publications
0
31
0
Order By: Relevance
“…Although both cytoplasmic and membrane proteins serve the purpose as therapeutic targets (Michael et al, 2014), membrane proteins are best suited for vaccine candidates (Baliga et al, 2018;Hasan et al, 2019a). Hence, in this study, membrane proteins (25) were used for vaccine construction, whereas cytoplasmic proteins (16) were proposed as suitable drug targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both cytoplasmic and membrane proteins serve the purpose as therapeutic targets (Michael et al, 2014), membrane proteins are best suited for vaccine candidates (Baliga et al, 2018;Hasan et al, 2019a). Hence, in this study, membrane proteins (25) were used for vaccine construction, whereas cytoplasmic proteins (16) were proposed as suitable drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…Several advantages help the researchers to select membrane proteins both as drug and vaccine candidates as their functions can be easily studied through computer-based approaches than wetlab process (Hasan et al, 2019a;Hasan et al, 2019b). In this study, two vaccine targets, 'Sensor histidine protein kinase UhpB (Q87HJ8)' and 'Flagellar hook-associated protein (Q87JH9)' were selected after screening the novel outer-membrane proteins (25) based on their antigenicity score and human microbiome non-homology analysis (Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…The allergenicity pattern of the predicted epitopes were determined through four servers i.e. AllerTOP (Dimitrov et al, 2013), AllergenFP (Dimitrov et al, 2014), Allergen Online (Goodman et al, 2016) and Allermatch (Fiers et al, 2004) were, while the toxicity level was demonstrated using ToxinPred server (Hasan et al, 2019b).…”
Section: Population Coverage Analysis Allergenicity Assessment and Tmentioning
confidence: 99%
“…Reverse vaccinology approach usually identified a protein vaccine candidate using defined features, such as protein subcellular localization, topology, adhesion/antigenicity probability, epitopes, and its binding to the major histocompatibility complex (MHC) class I and II molecule [34]. Reverse vaccinology approach has been proven to prioritize and design vaccine targets against multiple pathogens [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%